A Happy Life in a Different Religious Marriage Experience in Malang City - Edwind Satri Simatupang; Yohanes Endi (Institut Agama Islam Negeri (IAIN) Manado, 2023)
This research focuses on interfaith marriages in Malang City, lived by several families with loyalty. In general, interfaith marriages are often considered a way to indoctrinate people into joining a particular religion. Interfaith marriage amid multiculturalism is an effort to respect each other's differences, not differences. The city of Malang, one of the fertile land areas for the growth of major and world religions since the colonial era, is an example of cultivating tolerance and religious differences. This study aims to show that interfaith marriages foster an attitude of tolerance within the small community (family) to avoid various kinds of social friction in society. The view of interfaith marriage is the basis for appreciating religious values in differences and not differences. Interfaith marriage promotes individual rights and freedoms within the state and upholds the values and spirit of family harmony. This study uses qualitative field research. Data was collected through observation, interviews, and documentation, as well as being analyzed and conclusions drawn. This study found that families who live in interfaith marriages make families respect religious differences seen as guidelines that lead to good, righteous, and holy lives. Interfaith marriages appreciate differences, not differences, so that the seeds of freedom of rights for children emerge in guiding their life journey, especially relations with God in religious values. Happiness can be experienced with fidelity even though the marriage is of different religions.